GAMBARAN KADAR CD4 PENDERITA HIV/AIDS SEBELUM DAN SETELAH PEMBERIAN ANTIRETROVIRAL (ARV) DI RSUP DR M DJAMIL PADANG TAHUN 2015 - Eka Seba Marta (Menara Ilmu, 2019)
One treatment after infection HIV adalah Antiretroviral therapy. KeberhasilanARV indicator is the patient body weight increased, decreased viral load, does not occuropportunistic infections and increased CD4. Based on a survey conducted on 3 patientswith HIV / AIDS obtained before administration of ARV CD4 levels are very low (≤ 50mm³). Interest penelitian adalah to describe levels of CD4 HIV / AIDS before, after 6months, 1 year and 2 years of ARV provision in Dr M Djamil Padang 2015.This type of research is descriptive. The population of all HIV / AIDS patientswho also receive ARVs in January-September 2014 (205 people). The place of research inVCT clinic, sample of 67 people taken by simple random sampling, taken from thepatient's medical record using the format of the data fields, then processed and analyzedand presented in tabular form distribution.Results showed of 67 respondents, only 1 (1.5%) had a normal CD4 levels priorto the administration of ARVs. After 6 months of antiretrovirals, (80.6%) of respondentsincreased levels of CD4 and (19.4%) of respondents experienced a decline in CD4 levels.After 1 year of antiretrovirals, (83.6%) of respondents increased levels of CD4 and(16.4%) of respondents experienced a decline in CD4 levels. After 2 years ofantiretrovirals, (74.6%) of respondents increased levels of CD4 and (25.4%) of respondentsexperienced a decline in CD4 levels.Based on the above results, it can be concluded that the levels of CD4respondents experienced a good increase, but some respondents were of CD4 decline,therefore, is expected to educate health care workers about the importance of regularlytaking ARVs for people living with HIV to maintain the immune system of PLWHA.Reading List: 14 (2004-2014)Keywords: CD4 levels, ARV